A population follow-up study of patients who left an emergency department without being seen by a medical officer. Issue 3 (9th March 2007) - Mohsin, Mohammed; Forero, Roberto; Ieraci, Sue; Bauman, Adrian E; Young, Lis; Santiano, Nancy
Abstract : Objectives: To describe the population of emergency department patients who leave without being seen by a medical officer, to investigate the circumstances of their visit and to ascertain whether they subsequently receive alternative medical care. Methods: A follow-up study was conducted of patients who were initially triaged, but left without being seen by a medical officer between July 2003 and October 2003 in a tertiary referral hospital emergency department in Sydney, Australia. Emergency Department Information System data were reviewed for population demographics, presenting complaints and acuity rating of patients. Follow-up telephone interviews were conducted within 7 days after the patient left the emergency department. Results: During the study period, 8.6% (1272 of 14 741) of the emergency department patients left without seeing a doctor and 35.9% (457 of 1272) of these patients who walks out were contacted for follow-up. The results from bivariate and multivariate analyses showed that walkout rates significantly varied by sociodemographic and clinical characteristics of the patients. Young patients aged 0–29 years, and those with longer waiting time for triage and triaged as "less urgent" were more likely to walk out than others. Overcrowding in the emergency department had a significant association with walkout of patients. Prolonged waiting time was the most common reason for leaving emergency departments without being seen by a doctor. Only 12.7% (58 of 457) of the walkout patients revisited emergency departments within 7 days of their departure and of those who were subsequently admitted following their return to hospital accounted for 5.0% (23 of 457). Of the follow-up patients, 39.4% felt angry about their emergency department experiences. Conclusions: The number of patients who leave an emergency department without seeing a doctor is strongly correlated with waiting time for medical review. Achieving shorter emergency department waiting times is central to reducing the numbers of people leaving without being seen. The rate of patients who leave without being seen is also strongly correlated with triage category. These findings highlight the importance of accurate triaging, as this clearly influences waiting time. It is also likely that there are patients who benefit from the reassurance of the triage assessment, and therefore feel less urgency for medical review. These may be cases where immediate medical review is not essential. This area should be further explored. These results are important for planning and staffing health services. Decision makers should identify and target factors to minimise walkouts from public hospital emergency departments.